Reverend Addie Wyatt : Faith and the Fight for Labor, Gender, and Racial Equality - Walker-McWilliams, Marcia, 1984- (Book collections on Project MUSE., 2016)
"Reverend Addie Wyatt (1924-2012) was one of the most influential African American female labor leaders in the twentieth century. Wyatt lived in Chicago for most of her life and while there became a nationally known civil rights activist, ordained minister, and outspoken feminist. She was the first female president of a local chapter of the United Packinghouse Workers of America, worked alongside Reverend Martin Luther King Jr. in Alabama and during marches in Chicago, and Eleanor Roosevelt appointed her to the Protective Labor Legislation Committee of President Kennedy's Commission on the Status of Women. In this biography, Walker-McWilliams tells the story of the reverend's commitment to social justice, which fueled her activism and leadership in the American labor movement, while also setting her life story in the sociohistorical climate in which Wyatt emerged. Walker-McWilliams argues that what began for Wyatt as an individual journey to break away from poverty became a commitment to a collective struggle against economic, racial, and gender inequalities and a lifetime of organizing and activism. Based on oral histories, interviews conducted with Wyatt's colleagues and families, Wyatt's collection of personal papers, and extensive archival data, Walker-McWilliams illuminates the ways Wyatt grew into the roles of activist and leader as a result of personal experiences with poverty, racism, sexism, and discrimination, and developed a spiritual faith that refused to see these circumstances as immutable structural forces"--